An Econometric Test of Alternative Constraints on the Growth of of Underdeveloped Countries: A Comment: Reply - Weisskopf, Thomas E. (The Review of Economics and Statistics, 1973)
Thomas E. Weisskopf, An Econometric Test of Alternative Constraints on the Growth of of Underdeveloped Countries: A Comment: Reply, The Review of Economics and Statistics, Vol. 55, No. 1 (Feb., 1973), pp. 133-134